Influence of Cryopreservation on the Acrosome Reaction in Hucul Stallion Spermatozoa - Monika Bugno-Poniewierska; Monika Bielecka; Natalia Pietras; Barbara Kij-Mitka; Zenon Podstawski; Bogusława Długosz (Animals, 2025)
The Hucul horse is a Polish primitive breed with a small population size, which highlights the importance of preserving the genetic resources. The cryopreservation of semen is essential for creating gene banks, but its effect on the acrosome reaction in Hucul stallions has not yet been investigated. The acrosome reaction is one of the most important physiological events associated with the fertilization process. Therefore, our goal was to determine the level of acrosome reaction in chilled and frozen/thawed Hucul stallion semen using the FluoAcro test and the SCA® semen analysis system. We found that semen cryopreservation significantly reduced sperm motility and was associated with an increased percentage of acrosome-reacted spermatozoa. It should be noted, however, that, in this case, there was no negative control, and the results may reflect acrosomal damage rather than the elicited responses. Further validation of the methods with equine sperm and the inclusion of a control are recommended.